The Effect of Traditional Jump Rope Games on Leg Muscle Strength of Elementary Students - Hani Choerunisa; Rahmat Permana; Anggia Suci Pratiwi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2026)
This study aims to examine the effect of jump rope on leg muscle strength in physical education classes for sixth-grade elementary school students. Traditional games are movement-based activities designed to support students' physical development through active participation. A quantitative approach with a quasi-experimental nonequivalent control group design was used in this study. Participants were sixth-grade students divided into an experimental group (n = 23) and a control group (n = 24). The experimental group received physical education through the traditional jump-rope game, while the control group received conventional instruction. Before the analysis, normality and homogeneity tests were conducted to determine the appropriate statistical procedure. Leg muscle strength was measured using a vertical jump test administered at the pretest and posttest. Data analysis focused on group differences using the Mann–Whitney test on change scores (posttest–pretest). The Mann–Whitney test results showed a U value of 176,000, Z = -2.279, and a p-value of 0.023 (< 0.05), confirming a significant difference between the experimental and control groups. These findings indicate that the traditional jump-rope game is effective at increasing leg muscle strength. This study was limited to leg muscle strength; further research could explore the broader impact on other motor skills and across different educational contexts.